Organophosphorus poisoning: A retrospective study on clinical profile and outcomes in ICU - Nadia Rose,; Sowmya Madihalli Janardhan Iyengar,; Navaneethan NK,; Sarath Chandra B, (Asian Journal of Medical Sciences, 2023)
Background: Organophosphorus (OP) compounds are widely used in India as insecticides and contribute to both acute and chronic poisoning. Several parameters have been analyzed to evaluate the severity of poisoning and to prognosticate the outcome but contradictory results have been obtained from studies for example for the relationship between hypokalemia and outcome, pseudocholinesterase (PChE) levels, and outcome. Aims and Objectives: The objectives of this retrospective study were to explore the epidemiological characteristics and clinical profile of patients admitted to intensive care unit with OP poisoning and to evaluate the outcomes including complications, in hospital mortality, and the predictors of mortality. Materials and Methods: All the patients above 18 years admitted with a history of ingestion of OP poisoning during the study period were included in the study. Data were collected from case records. Results: The mean age of the patients was 34±13.54. Fifty-four patients were male (69.2%) and 24 were female (30.8%). The correlation coefficient between intubation and PChE levels was 0.266. The mean period of ventilation was 4.16 days±2.41 days. About 80% (n=20) put on ventilator survived. Correlation of hypokalemia with patients getting ventilator support was 0.26 and that with mortality was 0.038. Conclusion: OP poisoning cases were primarily noted in the younger male group with the intent to self-harm. Chlorpyrifos was the most common compound consumed. Early admission and appropriate treatment can reduce mortality and complications as there is no single factor which can be used to predict the outcome in these patients.